Os espaços de confinamento Persa - TAVARES, Jansen Hinkel M. (2017)
A study of films of Persian origin, which considers reduced film spaces as a possible clipping to address issues of arrest and control in their multiple appearances. Based on some audiovisual works by the Iranian filmmakers Jafar Panahi, Abbas Kiarostami and Samira Makhmalbaf, we seek to contextualize a spatial subtraction and its representation that reveal, respectively, political prison, social prison and private jail. It is, therefore, a social study of spaces, both their representation in the aesthetic field (the cinema, in the case), and the historical and cultural processes occurring in such spaces. By establishing the theoretical discussion between the cinema and the history of Iran, and perceiving the restrictions that an artistic production suffers within a theocratic regime; the text evidences, through the chosen films, the presence of the prison and the control in the esthetic proposal of such films, concerned with the interpretation of its society. That is, the variety of works analyzed gives analogical unity to research: the subtraction of space and the events given from the confinement. In addition, the philosophical interest in such works allows the understanding of social spaces from the point of view of cinema, which is, therefore, the main objective of this text.